Patterns and Trends in Cetacean Occurrence Revealed by Shorewatch, a Land-Based Citizen Science Program in Scotland (United Kingdom) - Gutiérrez-Muñoz, Paula; Walters, Alice E. M.; Dolman, Sarah J.; Pierce, Graham J. (Frontiers in Marine Science, 2021)
Shorewatch is a citizen science project, organised by WDC, that records the occurrence of cetaceans during regular standardised watches from a series of locations along the coast of Scotland. Observer training and a clearly defined protocol help deliver a valuable source of information about cetacean occurrence and activity along the coast. Since 2005, over 52000 watches have generated over 11000 sightings of at least 18 cetacean species. GAMs based on sightings for the five most commonly sighted species (bottlenose dolphin, harbour porpoise, minke whale, Risso’s dolphin and common dolphin), at those sites with the longest time series, demonstrated seasonal, geographical and year-to-year differences in their local occurrence and relative abundance. Bottlenose dolphins are mainly present at observation sites located on the east coast of Scotland, being uncommon on the west coast, while harbour porpoise and minke whale are principally present on the west coast. The seasonality observed in cetacean occurrence is consistent with peak abundance in summer months described by previous studies in the area. Mean depth around the observation sites is the static variable that apparently has the greatest influence on species presence and number of sightings, except for Risso’s dolphin. All the species except bottlenose dolphin showed upward trends in occurrence and number of sightings over the period 2012-2018. It was found evidence of temporal autocorrelation between results from consecutive watches at the same site on the same day as well as between results from consecutive days at the same site. The power to detect declines in local abundance over a 6-year period depends on the underlying sightings rate of each cetacean species, the number of watches performed and the rate of decline. Simulations performed to determine the power to detect a decline, suggest that the current intensity of observation effort in some observation sites, of about 2500 watches per year, may offer good prospects of detecting a 30% decline of the most frequently sighted species over a 6-year period, although a more even distribution of observation effort in space and time is desirable. The data could potentially be used for monitoring the status of cetacean populations.